PENDAMPINGAN MANAJEMEN KEUANGAN DAN PENCATATAN AKUNTANSI PT AIR MINUM SANGGAM BALANGAN - Kadir, Kadir; Yuliastina, Mellani; Stiadi, Doni; Nordiansyah, Muhammad; Haryanto, Haryanto; Yusnita, Yusnita (MAJU : Indonesian Journal of Community Empowerment, 2024)
The development and desirability of a business and economic activity is highly dependent on effective financial management, which aims to maximize the value of research through strategic decision making. The transformation of PT Air Minum Sanggam Balangan from a Regionally Owned Enterprise (BUMD) to a limited liability company in 2023 through Balangan Regency Regional Regulation (PERDA) Number 1 of 2023 has brought significant changes to the company's operations and financial management. As companies navigate this transition, providing a comprehensive understanding of financial management and accounting practices will be critical to ensuring long-term desirability and success. Activities are carried out in three stages, namely initial survey, implementation and evaluation. This service takes a consultative and collaborative learning approach. The evaluation results after partner activities receive assistance, partners are able to understand and make better financial planning, manage cash more effectively, analyze financial performance, choose the right investment, manage loans and debts, manage assets and depreciation, and manage better financial risks.